Comparison of thermal stabilities of p+-Si/p-diamond heterojunction and Al/p-diamond Schottky barrier diodes. (1st June 2022) - Uehigashi, Yota; Ohmagari, Shinya; Umezawa, Hitoshi; Yamada, Hideaki; Liang, Jianbo; Shigekawa, Naoteru
Abstract: We evaluate the current–voltage ( I–V ) and temperature-dependent I–V characteristics of p + -Si/p-diamond heterojunction diodes (HDs) fabricated using surface-activated bonding and compare their characteristics with those of Al/p-diamond Schottky barrier diodes (SBDs) fabricated on the same diamond substrate. The ideality factor, reverse-bias current, and on/off ratio of HDs are improved by annealing them at temperatures up to 873 K, which is in good contrast to the characteristics of SBDs. The barrier height at Si/diamond bonding interfaces is decreased by annealing. The difference in response to annealing between HDs and SBDs implies that the density of interface states formed during the surface activation process is decreased by annealing HDs. The characteristics of HDs are degraded by annealing them at 1073 K, which is assumed to be due to the formation of intermediate layers or the occurrence of local strain at Si/diamond bonding interfaces.